Barriers and facilitators of community-based nursing development: A scoping review - Naiemeh Seyedfatemi; Hamid Peyrovi; Salime Goharinezhad; Saeid Hossein Oghli (Journal of Education and Health Promotion)
In the last few decades, chronic diseases have spread and new and emerging health and social issues have affected people’s health. COVID-19 and other emerging and re-emerging diseases are creating new challenges for societies that affect how healthcare is managed. It is through the development of community-based nursing that some of these problems can be solved. This study was conducted to identify barriers and facilitators of community-based nursing development. To determine the type, extent, and nature of research conducted on barriers and facilitators of CBN, a scoping review was conducted, and five databases (ProQuest, PubMed, CINAHL, Scopus, and Web of Science) were systematically searched during the years 2000–2023. Relevant articles were extracted according to the inclusion criteria (studies related to community-based nursing dimensions published in English). The articles were reviewed in terms of title, summary, and relevant content, and finally, 22 articles remained. Then, 22 articles were analyzed by the thematic analysis method. Education, promoting cultural sensitivities, planning and reforming health policies, increasing public awareness for community-based nursing, providing more care experiences and opportunities, and improving community-based nursing service delivery approache. The obstacles to the development of community-oriented nursing in four categories included weak organizational power, job burnout, false beliefs and expectations, and the negative influence of the media. Based on the results of this review, reforming existing policies with an emphasis on culture building, education, and public awareness, and, the other hand, trying to remove obstacles with the help of the media and correcting public beliefs are among the important measures that can be taken in the field of community-oriented nursing development.